2018
DOI: 10.7717/peerj.5004
|View full text |Cite
|
Sign up to set email alerts
|

Is perfectionism associated with academic burnout through repetitive negative thinking?

Abstract: Academic burnout is prevalent among university students, although understanding of what predicts burnout is limited. This study aimed to test the direct and indirect relationship between two dimensions of perfectionism (Perfectionistic Concerns and Perfectionistic Strivings) and the three elements of Academic Burnout (Exhaustion, Inadequacy, and Cynicism) through Repetitive Negative Thinking. In a cross-sectional survey, undergraduate students (n = 126, Mage = 23.64, 79% female) completed well-validated measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 48 publications
3
12
0
1
Order By: Relevance
“…Several authors have indeed noted that the role of parents in students' study and career choices has been under-researched (Jodl et al, 2001;Taylor et al, 2004), but choosing one's study and career path according to one's own preferences is likely to be more satisfying than living the life that others have in mind for one. Recently, it has been noted that especially "socially prescribed" perfectionism where people try to live up to the standards of other and also seek their approval is related to burn-out, depression and a lack of experienced meaning (Suh et al, 2017;Garratt-Reed et al, 2018;Curran and Hill, 2019). In our society, education is highly valued, but less emphasis is placed on structured reflection about values, goals, and plans for what people want in life.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have indeed noted that the role of parents in students' study and career choices has been under-researched (Jodl et al, 2001;Taylor et al, 2004), but choosing one's study and career path according to one's own preferences is likely to be more satisfying than living the life that others have in mind for one. Recently, it has been noted that especially "socially prescribed" perfectionism where people try to live up to the standards of other and also seek their approval is related to burn-out, depression and a lack of experienced meaning (Suh et al, 2017;Garratt-Reed et al, 2018;Curran and Hill, 2019). In our society, education is highly valued, but less emphasis is placed on structured reflection about values, goals, and plans for what people want in life.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is not surprising for adaptive perfectionists to have positive outcomes such as positive affect, better academic achievement, effective problem solving, better life satisfaction (Bergman, Nyland, & Burns, 2007;Hicks & Yao, 2015) and maladaptive perfectionists to have negative outcomes involving depression, anxiety, suicidal ideation, low selfworth, self-criticism, and so on (Kiamanesh, Dieserud, & Haavind, 2015;Meh & Adams, 2016). Among other negative outcomes, maladaptive perfectionism has been frequently linked with burnout in student population and in others as well (Aboalshamat et al, 2017;Garratte-Reed, Howell, Hayes, & Boyes, 2018;Zhang, Gan, & Cham, 2007).…”
mentioning
confidence: 99%
“…Previous research (e.g., Chang et al 2016;Garratt-Reed et al 2018;Luo et al 2016) has reported a negative association between perfectionistic strivings and academic burnout. For example, Chang et al (2016) found that perfectionistic strivings were negatively associated with academic burnout through high levels of intrinsic and identified motivation.…”
Section: Association Between Perfectionism and Academic Burnoutmentioning
confidence: 83%
“…For example, Chang and Lee (2020) reported that perfectionistic concerns predicted low levels of goal reengagement, which was linked to high levels of academic burnout. Garratt-Reed et al (2018) found a positive association between perfectionistic concerns and academic burnout through high levels of repetitive negative thoughts. Lee and Yang (2019) showed that perfectionistic concerns have a positive association with academic burnout through low levels of internal locus of control and self-encouragement.…”
Section: Association Between Perfectionism and Academic Burnoutmentioning
confidence: 89%